Being small at the right moment: Path dependence after a shift in the technological regime - Jasper Hepp (Bielefeld University, Faculty of Business Administration and Economics, 2021)
This paper explores the impact of technological change on industry concentration and the underlying firm dynamics. In the agent-based model EURACE@Unibi I implement a paradigm shift in the technological frontier - a shift from a slow to a fast growing regime. The analysis shows that the acceleration in technological change causes a strong increase in market concentration. The reallocation of market shares towards a few large firms is driven by diverging productivities and skills across firms. An ex-post analysis reveals that after the paradigm shift small, but undervalued firms become the large dominating ones in the long-run. Their success gets initiated by a fortunate outcome on the labor market, which increases their skill level. With the faster technological change, their high skilled workforce incentivizes them to invest at the frontier and to build up the most productive capital stock. A virtuous cycle between their decisions on the labor and capital market further increases the productivity gap towards competitors enabling their rise.
urn:nbn:de:0070-pub-29503516
Keywords: C63; O33; L10; 330; Market Concentration; Technological Paradigm Shift; Path Dependency; Firm Determinants; Agent-Based Model; Technischer Fortschritt; Unternehmenskonzentration; Dynamische Kompetenzen; Pfadabhängigkeit; Prinzipal-Agent-Theorie; Investitionsgüter